Acquit Et De Charge to the Responsibilities of the Management of Limited Liability Companies - Aisyah, Rizka Rahadiyani; Prasetyo, Handoyo; Fahrozi, Muhammad Helmi; Surahmad, Surahmad (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The form of a limited liability company is the most widely used form of economic activity today. In the General Meeting of Shareholders, the Managements and Commissioners in realizing the accountability for what they have done in one financial year, are obliged to submit an annual report. With the approval of the annual report responsibilities from the Board of Directors, the Managements gets "acquit et de charge" (release and settlement). This research uses the statutory approach method and the conceptual approach method with data collection by means of literature study, namely studying and systematically analyzing, books, scientific works, and legislation. The result of this research is that the principle of acquit et de charge does not eliminate the Managements from criminal responsibility. This can be seen from Article 155 of the Limited Liability Company Law and there is no guarantee that this principle can free oneself from criminal responsibility against the Board of Directors. However, with the Business Judgment Rule (BJR) as a legal protection which has the condition that as long as the Managements prioritizes the principle of prudence, good faith and full responsibility.